FACTORS THAT LEAD TO MISINTERPRETATION OF ELEVATED MEAN PLATELET VOLUME LEVELS IN VARICOCELE PATIENTS: A NARRATIVE REVIEW - Arshad, Muhammad Asharib; Ahmad, Muhammad Raza; Arshad, Wajeeha; Ullah, Irfan; Zil-E-Ali, Ahsan (Annals of Allied Health Sciences, 2019)
Varicocele is a condition characterized by abnormal dilation of the pampiniform plexus. It is estimated to have a prevalence of approximately 10– 15% among males, between 19–41% in men who are suffering from primary infertility, and around 80% in those with secondary infertility. A lot of work has been done to delve into the etiology of a varicocele, but to date the subject remains poorly understood. Necessitating further research regarding this topic is the fact that varicocele has been linked to many other vascular pathologies. First of all, it is important to note that MPV is not directly associated with or a measure of platelet function in any way. Thus, these measurements of platelet indices such as mean platelet volume and PDW are not indicators of platelet function. Currently, a measure of platelet aggregation is the gold standard when platelet function is to be assessed. A study was done to check for links, but it did not find there to any correlation between platelet indices such as platelet count, mean platelet volume, platelet distribution width and that of platelet aggregation, which measures platelet function, such as platelet response with collagen, adenosine diphosphate and epinephrine which were recorded with the use of light transmission turbid metric platelet aggregometry in individuals deemed to be healthy. Studies attempting to figure out the correlation between mean platelet volume and chronic inflammatory disease have found that greater mean platelet volume was observed among those suffering from rheumatoid arthritis particularly in the active phase and the inflammatory markers were elevated.